PERANAN DAN FUNGSI MANAJEMEN BAGI KEPALA SEKOLAH - Lubis, Rosimah (IAIN Padangsidimpuan, 2013)
Management covers onÂ planning, organizing, actuating,Â and controlling.Â A headmaster as the educational organizer must pay attention on the elements of management in order his or her institution can provide a good and satisfied result. That will be effective and efficient to increase human resource and be functional and proportional to all elements of the management.